Comparative descriptive study of selective filtration models for selective attention - BENCHAKHCHOUKH, Asma; DJENNANE, Amine (Journal of Human Sciences, 2020)
The study aims to describe and compare the selective filtering models of selective attention: Broadbent model (1985), Deutsch-Deutsch (1963), Treisman (1964), Johnston et Hienz (1978). Each model has its own point of view, pointing to the most important criticisms it carries, as well as the most common and different points between the model and the other, with the introduction of a new idea presented as a proposed model that combines the missing links we have seen in each model, Selective composite stimuli have special optical ones, which combine between of filtering and his whereabouts.